An enhancer haplotype may influence BCL11A expression levels and the response to hydroxyurea in β-thalassemia patients. (July 2017) - Maroofi, Nahal; Azarkeivan, Azita; Banihashemi, Soosan; Mohammadparast, Saeid; Aghajanirefah, Ali; Banan, Mehdi
Aim: To identify the BCL11A intron-2 enhancer linkage disequilibrium (LD) block, harboring two previously identified SNPs, associating with the hydroxyurea response in β-thalassemia patients and the functional significance of this region.Materials & methods: Several neighboring SNPs were genotyped in our cohort. The associating LD block was identified, and its function studied in K562 erythroid cells via CRISPR/Cas9 genome editing.Results: A haplotype harboring three tag SNPs correlated significantly with the HU-response and BCL11A transcript levels in the patients' reticulocytes. Two deletions encompassing this LD block significantly reduced BCL11A transcript levels in K562 cells.Conclusion: Our data suggest an essential role for this LD block in BCL11A expression levels and the response to hydroxyurea in β-thalassemia patients.